Dr. Jonathan Dunne — Deep Plane Facelift — London - Dunne, Jonathan (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Jonathan Dunne, practicing in London, UK. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003170; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; uk; london